Green Data Centers as Strategic Assets: A Bibliometric Review of Energy Efficiency, ESG, and Competitive Advantage - Noor, Rinaldi; Sofia, Alfira; Wibowo, Lili Adi; Arisandi, Desi (International Journal of Energy Economics and Policy, 2025)
The rapid expansion of digital infrastructure has positioned data centers as critical components of the digital economy while intensifying concerns over energy consumption and environmental sustainability. In response, a growing body of research has examined green data centers as a means of improving energy efficiency; however, strategic and governance perspectives remain fragmented. This study aims to systematically map the intellectual, conceptual, and thematic development of green data center research, with particular attention to its links with energy efficiency, environmental, social, and governance considerations, and competitive advantage. Using a systematic literature review combined with bibliometric analysis, this study analyzes 1,431 Scopus-indexed journal articles published between 2015 and 2025. The analysis employs descriptive performance indicators, citation and co-citation analysis, co-word analysis, thematic mapping, thematic evolution, and bibliographic coupling using Biblioshiny. The results reveal a sharp increase in publications after 2020, reflecting heightened academic and policy attention to the energy intensity of data centers. The intellectual structure of the field is dominated by highly cited studies on the optimization of computing systems and energy efficiency. At the same time, co-word and thematic analyses identify energy efficiency and green computing as core driving themes. Thematic evolution indicates a consolidation toward data center–focused research, yet strategic management and environmental, social, and governance perspectives remain weakly integrated. Overall, the findings suggest that green data centers are still primarily conceptualized as technical solutions rather than as strategic assets embedded within organizational sustainability strategies.